Political economy of the US financial crisis 2007-2009 - Vuk Vuković (Financial Theory and Practice, 2011)
The emphasis of this paper is on the political economy of the subprime mortgage crisis in the United States and how the policy makers contributed to it through their legislation and regulations, made under the rising influence of interest groups and the lobbying activities of the finance industry. The “Great Recession” of 2007-2009 began as a bubble-burst in the mortgage market in the United States that spilled over to the entire financial market of the US, and afterwards to the integrated world financial market. The crisis sprang up over the US real sector and, due to the decline in US aggregate demand, spread consequently to the real economy of the rest of the World. No sound evidence has been given for the publicly proclaimed idea that the causes of the crisis lie within the self-regulating free market. The causes of the crisis lie primarily in the activities of political power, i.e. in the extensive government regulation which has, under the strong influence of interest groups and the lobbying power of financial corporations, led to favouritism in macroeconomic policies and inefficient resource allocation. Regulation was enforced by stimulating affordable housing through government sponsored enterprises, oligopoly of the rating agencies, banking regulation and an increasing connection between government and the finance industry.